The “What” and the “How” of Dispositional Mindfulness: Using Interactions Among Subscales of the Five-Facet Mindfulness Questionnaire to Understand Its Relation To Substance Use - Eisenlohr-Moul, Tory A. (2012)
Although self-report measures of dispositional mindfulness have good psychometric properties, a few studies have shown unexpected positive correlations between substance use and mindfulness scales measuring observation of present-moment experience. The current study tested the hypothesis that the relationship between present-moment observation and substance use is moderated by the tendency to be nonjudgmental and nonreactive toward the observed stimuli. Two hundred and ninety-six undergraduates completed the Five-Facet Mindfulness Questionnaire (FFMQ), a calendar measuring periods of substance use, and a measure of the Five-Factor Model of personality. Controlling for FFMQ and personality subscales, significant interactions between the observing and nonreactivity subscales indicated that the observing subscale was negatively associated with substance use at higher levels of nonreactivity but positively associated with periods of substance use at lower levels of nonreactivity. Results support the use of statistical interactions among FFMQ subscales to test for the presence of interactive effects of different aspects of mindfulness.